Discovery and description of a new species of burrowing frog Sphaerotheca Günther, 1859 (Anura: Dicroglossidae) from the suburban landscapes of Bengaluru, India - Deepak, P.; Dinesh, K.p.; Nag, K.s. Chetan; Ohler, Annemarie; Shanker, Kartik; Souza, Princia D; Prasad, Vishal Kumar; Ashadevi, J.s. (Zootaxa, 2024)
Recent resolution of prevailing taxonomic ambiguities in the genus Sphaerotheca and new species discoveries from urban/suburban landscapes highlight the need for attention to non-forested habitats for amphibian conservation. In this paper, we review the status of the members of the genus Sphaerotheca and justify the synonymy of Sphaerotheca magadha as a junior synonym of Sphaerotheca swani. The prospects of resurrection of Sphaerotheca swani (herein preliminarily referred to as Sphaerotheca cf. breviceps [swani]) are discussed. In addition, we describe a new species Sphaerotheca varshaabhu sp. nov. from the suburban region of Bengaluru, India. We employ an integrative taxonomic approach to characterize the new species using molecular phylogeny, genetic distance, morphological characters, and geographical isolation as lines of evidence. We also provide a description of vocal repertoire of Sphaerotheca varshaabhu sp. nov. and provide comparative bioacoustics data for four species. This previously undescribed species from the suburban areas of Bengaluru described herein as Sphaerotheca varshaabhu sp. nov. forms a genetically divergent lineage and its genetic distance varied from 3.6% to 12.2% for 16S rRNA with respect to other species of Sphaerotheca. Our phylogenetic analysis for the genus including the new species confirms the synonymy of one recently described species, resulting in 10 valid species in the genus Sphaerotheca. These results emphasize the need for utilizing an integrative taxonomic approach for uncovering hidden diversity of suburban areas. Given these recent discoveries, we advocate for more robust surveys in human dominated areas, so that these amphibians may receive more attention.